Lumiflavin Reduces Cisplatin Resistance in Cancer Stem-Like Cells of OVCAR-3 Cell Line by Inducing Differentiation - Yang, Ruhui; Liu, Bingjin; Yang, Mingyue; Xu, Feng; Wu, Songquan; Zhao, Shufang (Frontiers in Oncology, 2022)
Ovarian cancer stem-like cells (CSCs) play a vital role in drug resistance and recurrence of ovarian cancer. Inducing phenotypic differentiation is an important strategy to enhance the effects of chemotherapy and reduce the drug resistance of CSCs. This study found that lumiflavin, a riboflavin decomposition product, reduced the development of CSC resistance and enhanced the chemotherapy effect of cisplatin (DDP) on CSCs in DDP-resistant ovarian cancer OVCAR-3 cell line (CSCs/DDP) and was related to the induction of CSC phenotypic differentiation. Results showed that the development of DDP-resistant OVCAR-3 cells was related to the increase in the proportion of CSCs/DDP, and the treatment with lumiflavin reduced the DDP-resistance levels of OVCAR-3 cells and proportion of CSCs/DDP. Further investigation found that lumiflavin synergistic with DDP increased apoptosis, decreased mitochondrial membrane potential, and inhibited the clonal formation of CSCs/DDP. Meanwhile, in vivo experiments showed that lumiflavin dose-dependently enhanced the chemotherapy effect of DDP on tumor-bearing nude mice inoculated by CSCs/DDP. Lumiflavin treatment also reduced the ratio of CD133+/CD177+ to CD44+/CD24 cells, which is the identification of CSCs, in CSCs/DDP. In addition, transcriptome sequencing results suggested that the role of lumiflavin was related to the notch and stem cell pathway, and Western blot analysis showed that lumiflavin inhibited the protein expression of notch signaling pathway in CSCs/DDP. In conclusion, lumiflavin reduces the development of the drug resistance of OVCAR-3 cell and increases the sensitivity of CSCs/DDP to DDP by inducing phenotypic differentiation, which may have a potential role in the chemotherapy treatment of ovarian cancer.